Radiação UV-B e adubação silicatada sobre a morfologia, fisiologia e bioquímica de dois genótipos de Theobroma cacao L. (Malvaceae) - Zanetti, Leonardo Valandro (2017)
Several studies report the ultraviolet-B (UV-B) damaging effects on the growth and fundamental physiological processes from several species of cultivated plants. However, species have variable sensitivity to UV-B radiation, and silicon (Si) can act as reliever agent stress caused by this type of radiation, resulting in some cases in increased growth. Cacao (Theobroma cacao L.) is considered one of the most important perennial crops because its seeds are the raw material for chocolate production. The cacao crop that is traditionally held in the shade, has given rise to growing in full sun, due to the higher productivity of plants in this condition, however, with higher maintenance costs. The plants in full sun are fully exposed to UV-B radiation which can damage the plant development. Technologies that enable higher performance of plants to stressful conditions is of great interest to producers, and in this context, silicon appears to be promising for presenting positive effects on plants in various environmental stresses. Based on growth, foliar anatomy and physiological and biochemical changes, the effects of UV-B radiation on leaves of two cacao genotypes (Catongo and PH16) with contrasting anthocyanin coloration were evaluated. Identified the most susceptible genotype to UV-B, it was determined the interactive effects of this radiation with plants fertilized with silicon, in order to determine a possible Si actions as reliever agent to UV-B. Finally, we investigated the location, morphology and chemical composition of the leaf crystals found in genotypes Catongo T. cacao, verifying the possible composition of some silicate crystals. For this, cacao seedlings of two genotypes, Catongo and PH16, were kept in controlled growth conditions for 42 days, being submitted to two levels of UV-B (0 and 3 KJ m-2 day-1 ) and two concentrations of Si at fertilization (0 and 2 mM). The Catongo genotype was characterized as the most susceptible and was therefore the genotype selected to evaluate the effect of Si on plants exposed to UV-B radiation. Leaf growth, foliar anatomy, gas exchange, chlorophyll fluorescence, photosynthetic pigments, polyphenols, soluble carbohydrates, lignin, mucilage, antioxidant enzymes, hydrogen peroxide and malondialdehyde content and silicon content were analyzed. In addition, leaf sections and isolated crystals were analyzed by means of transmissible and polarized light microscopy and scanning electron microscopy, and crystals chemical composition was determined by histochemical tests, X-ray microanalysis and Raman spectroscopy. The data showed that both genotypes suffered leaf damage with exposure to UV-B radiation, however it was more evident in the Catongo genotype, which showed a high energy cost with metabolic alterations. In contrast, the PH16 genotype showed tolerance to UV-B radiation, presenting higher energy efficiency with a high biomass gain. The evaluation of Si effect on Catongo plants submitted to UV-B, showed that the silicate fertilization acted in a regulated way with the radiation, providing energy savings by reducing carbon consumption from respiration and productions the chlorophyll pigments, anthocyanins, flavonoids and phenols, leading to a greater accumulation of biomass. Finally, the investigations related to the T. cacao leaf crystals revealed a high diversity of shapes and chemical composition on the observed crystals such as calcium oxalate, silica or a mixture of these two.